The Role of Memory in Maintaining the Sense of Place in Traditional Houses; Case of Famagusta Walled City - Ramezani, Hoda (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The sense of place has been found in many various ways. We frequently have a sense of place about where we live, or where we lived when we were kids. The compound and complex mental, effective, and evaluative relationships people progress with interpersonal and environmental groups by using a behavior can be defined by a sense of place. The sense of place is hence an element of place that grows from feelings connected to experience and is collected not only of physical essentials, but also movement, meaning, and place attachment. A sense of place rises through a comprehension of the chronicles, topography, and geography of an area, its tendency, the legends of an area, and a regularly developing feeling of the land and its own experience subsequent to living there for some time. A sense of place rises through a comprehension of the chronicles, topography, and geography of an area, its tendency, the legends of an area, and a regularly developing feeling of the land and its own experience subsequent to living there for some time. Remembrances of personal and ethical encounters as time passes make a location special. Some factors as body condition, tunes or dances that emerge from the folk of a location, some special skills can help define a location and show the sense of place. Through time, experiences as a background help people that transmit thoughts of place from area to a generation. Focusing on how the sense of place evolves and changes is pertinent to focus on how people connect to their environment generally speaking and considering how this discussion could become more sustainable. Hence, this thesis tries to make a better understanding of the role of memory in maintaining a sense of place in traditional houses. Initially, qualitative methods were used for data collection. For understanding a sense of place requires to know the culture and understanding a memory that requires a human experience, with documentary research in architecture, it tried to find articles which are related to the topic and continued by defining some factors of which one is effective in memory creating a sense of place. Then, some important keywords were extracted, placed and arranged in a table and examined in the case study. As for the case study, the Walled City of Famagusta, located in North Cyprus, has been studied. For better results, two houses were chosen that have old owner residents who lived there for a long time. These houses are being used now and they were selected from each zone. Finally, the conclusion of all findings is shown. The memory of sense of place, sensation and cognitive experience are the most important points, and comprise cultural opinions or beliefs and practices that make connection between people and place end up helping to architects who are paying attention to the use of memory and sense of place, creating a valuable place. New key words would be suggested. Keywords: space, place, sense of place, memory, home, Cyprus

ÖZ: Yer duygusu çeşitli şekillerde bulunan bir kavramdır. An itibariyle veya çocukken yaşadığımız yere karşı sık sık aidiyet duyarız. İnsanların kişilerarası ve çevresel gruplardaki gelişimine katkıda bulunan etkili, değerlendirici, bileşik ve karışık zihinsel ilişkiler yer duygusuyla tanımlanabilir. Dolayısıyla yer duygusu yalnızca fiziksel gerekliliklerden değil, aynı zamanda hareket, anlam ve bir yere bağlılıktan çıkarılan, tecrübelere bağlı duygulardan oluşan bir yer unsurudur. Yer duygusu bir bölgenin geçmişini, topoğrafyasını ve coğrafyasını, eğimini, harita özelliklerini anlayarak ve o bölgede belirli bir süre zarfınca yaşamaya bağlı olarak bölgeye ve bölgeye has tecrübelere karşı beslenen duygularla oluşur. Zaman geçtikçe bölgenin insanlarıyla ve gelenekleriyle ilgili oluşan hatıralar o bölgeyi özel yapar. Vücut kondisyonu, halka ait ezgiler veya danslar belirli beceriler gibi bazı faktörler bir bölgeyi tanımlamaya ve yer duygusunu göstermeye yardımcı olabilir. Zamanla özgeçmiş haline gelen tecrübeler insanların bir yer ile ilintili düşüncelerini bir bölgeden bir nesile iletmesine katkıda bulunur. Yer duygusunun nasıl değiştiğini ve geliştiğini anlamak, insanların çevresiyle genel olarak nasıl bağ kurduklarıyla ve bu tartışmaların daha sürdürülebilir hale getirilmesiyle ilgilidir. Dolayısıyla bu tez, geleneksel evlerde anıların, yer duygusunun korunmasındaki rolünü daha anlaşılır hale getirmeyi amaçlar. Başlangıçta, niteliksel metotlar bilgi toplamak için kullanıldı. Yer duygusunun anlaşılması için mimari belgelere dayanan araştırmalarla, insan deneyimlerinin gerektirdiği anıların ve kültürün bilinmesi gerekmektedir. Bu araştırmalar, yer duygusuna bağlı olarak oluşan anıların etkilerinden biri olan, tanımlanmış bazı faktörler tarafından devam eden ve konuyla ilişkili olan makaleler bulmak için yapılmıştır. Daha sonra,vaka analizinde bazı anahtar kelimeler çıkarılmış ve bir tabloya koyulup yerleştirilmiştir. Vaka analizinde, Kuzey Kıbrıs’ta yer alan etrafı surlarla çevrili Gazimağusa Surlariçi çalışıldı. Daha iyi sonuçlar almak için sahiplerinin uzun süredir içinde yaşadığı iki ev seçildi. Her bölgeden seçilen evler hala kullanılmaktadır. Son olarak, bütün bulguların sonucu gösterilmiştir. Yer duygusu ile ilgili anılar, duyusal ve bilişsel deneyimler en önemli noktalardır. Kalıplaşmış kültürel düşünceler, inançlar ve yer arasında bağlantı kuran çalışmalar hafıza kullanımı ve yer duygusuyla ilgilenen, mimari değerler tasarlayan mimarlara katkıda bulunmaktadır. Yeni anahtar kelimeler önerilmiştir. Anahtar kelimeler: uzay, yer, yer duygusu, hafıza, ev, Kıbrıs
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2018. Supervisor: Assoc. Prof. Dr. Rafooneh Mokhtar Shahi Sani.
Keywords: Architecture; Architecture, Domestic--Famagusta Walled City--Famagusta (Cyprus, North); Vernacular Architecture--Traditional Houses--Famagusta Walled City--Famagusta (Cyprus, North); Senses and sensation in architecture; Space; Place; Sense of Place; Memory; Home; Cyprus